Implantation of 3D Constructs Embedded with Oral Mucosa-Derived Cells Induces Functional Recovery in Rats with Complete Spinal Cord Transection - Ganz, Javier; Shor, Erez; Guo, Shaowei; Sheinin, Anton; Arie, Ina; Michaelevski, Izhak; Pitaru, Sandu; Offen, Daniel; Levenberg, Shulamit (Frontiers in Neuroscience, 2017)
Spinal cord injury, involving damaged axons and glial scar tissue, often culminates in irreversible impairments. Achieving substantial recovery following complete spinal cord transection remains an unmet challenge. Here, we report of implantation of an engineered 3D construct embedded with human oral mucosa stem cells (hOMSC) induced to secrete neuroprotective, immunomodulatory and axonal elongation-associated factors, in a complete spinal cord transection rat model. Rats implanted with induced tissue engineering constructs regained fine motor control, coordination and walking pattern in sharp contrast to the untreated group that remained paralyzed (42% vs. 0%). Immunofluorescence, CLARITY, MRI and electrophysiological assessments demonstrated a reconnection bridging the injured area, as well as presence of increased number of myelinated axons, neural precursors, and reduced glial scar tissue in recovered animals treated with the induced cell-embedded constructs. Finally, this construct is made of bio-compatible, clinically approved materials and utilizes a safe and easily extractable cell population. The results warrant further research with regards to the effectiveness of this treatment in addressing spinal cord injury.